(untitled) (UNIZIK Journal of STM Education, 2025)
This study investigated the effects of Experiential Learning Approach (ELA) on secondary school students’ academic achievement in biology in Udi Education Zone of Enugu State. The study adopted a quasi-experimental, non-equivalent pretest-posttest control group design with a 2x2 factorial structure. The population of the study comprised of 1784 (792 males and 992 females) senior secondary school two (SS2) biology students in all the government co educational secondary schools in Udi Education Zone of Enugu State. A total of 84 (44 males and 40 females) SS2 biology students from two co-educational secondary schools were purposively selected and randomly assigned to experimental group and control group. The study was guided by two research questions and three null hypotheses, tested at a 0.05 level of significance. The instrument used for data collection was Biology Achievement Test (BAT), validated by three experts with reliability coefficients determined using Kuder-Richardson 20 (KR-20) and yielding a value of 0.82. Mean and standard deviation were used to answer the research questions, while Analysis of Covariance (ANCOVA) was employed to test the hypotheses. Findings revealed that students taught Biology using ELA significantly outperformed those taught using LM in their academic achievement in Biology. Gender did not significantly influence achievement in Biology and there was no significant interaction effect between teaching method and gender on achievement of students in Biology. The study concluded that ELA enhances students’ achievement in biology more effectively than lecture method. Based on the findings, it was recommended that biology teachers should integrate ELA into instructional practices and those curriculum developers and education stakeholders consider ELA to improve science education outcomes.